If not Bogomilism than What? The Origins of Catharism in the Light of the Sources - Czarnecki, Piotr (Studia Ceranea, 2021)
Since the end of the twentieth Century the traditional interpretation of Catharism, assuming it’s Eastern roots and dualist character is the object of a harsh criticism, formulated by the deconstructionist scholars. The moderated version of their new interpretation assumes that dualism didn’t play an important role in Catharism, and that the Cathar “dissidence” was not influenced by the Eastern dualist heresies (especially Bogomilism), but appeared independently in the West. According to the radical version Catharism didn’t exist at all and contemporary scholars should accept a new paradigm – Middle-Ages without Catharism. The aim of this article is to examine the source arguments, which stand behind both interpretations – on one side the arguments concerning the contacts of the Cahars with the Eastern dualists, with special attention paid to the time of their emergence and character of these relations, and on the other the arguments concerning Cathar dualist doctrines, which according to the deconstructionists were constructed arbitrarily by the Catholic polemists, basing on the ancient anti-heretical works, especially anti-Manichaean writings of St. Augustine. The article will try to find the answer to the question if the Cathar doctrines described in the Catholic sources are indeed so closely similar to the Manichaean teachings known from St. Augustine and at the same time so different from the Bogomil dualism. The analysis of the sources will show if the new interpretation is based on the arguments that are strong enough to overthrow the traditional one and if it the theory assuming lack of Bogomil influence can be considered as a serious alternative.